The Role of Islamic Ethics in Shaping Resilient Social and Economic Systems - Marwa, Nabilah; Mustika, Nisa (Yayasan Sinergi Kawula Muda, 2024)
This narrative review explores the interplay between social, economic, and policy dimensions in fostering adaptive and sustainable Islamic civilizations. Anchored in Islamic ethical principles, the study examines how collective identity, economic development, and value-driven governance shape societal resilience. Utilizing a comprehensive literature review method, the analysis synthesizes empirical, historical, and policy-based findings from various geographical and cultural contexts. Results show that social cohesion, facilitated by family structures and religious values, plays a critical role in enhancing psychological and community resilience. Economically, equitable resource distribution and infrastructural investment emerge as key determinants of public service quality. On the policy front, governance models rooted in Islamic justice significantly enhance accountability and public trust. The discussion highlights that the integration of these dimensions forms a systemic framework for sustainable development. It emphasizes the importance of overcoming institutional inefficiencies, economic disparities, and limited public engagement through contextually adaptive, interdisciplinary policies. The study underscores the urgency of aligning traditional values with modern systems and recommends continuous participatory evaluation as a best practice. These insights contribute to advancing holistic frameworks for Islamic civilization-building and propose directions for further research on context-specific implementations of integrative development strategies.